Using “Spontaneous Geography” to reason about environmental problems - Cédric Naudet (European Journal of Geography)
Climate change is a major challenge for societies, especially for future generations. Since 2018 and the large protests initiated by Greta Thunberg, an international youth protest movement has emerged in favour of action against climate change. Yet recent surveys have shown that, despite being aware of these issues, young people’s level of analysis of climate phenomena and their capacity for abstraction to understand environmental issues remain low. Consequently, developing didactic scenarios which enable students to understand this complexity appears to be a significant challenge in teaching curricula. Our hypothesis is that drawing on concrete situations presenting the actions of geographical agents would make it possible to overcome the barriers of abstraction. The "Spatial Thinking" group of the Paris-Cité University has formalized an experiential geography based on learning theories which show that learning is a process that can only take place by going back and forth between what the student knows and what they learn. This article first presents a teaching scenario designed to facilitate the teaching of environmental issues. It then examines the results obtained by the students and the new abstraction capacities offered to them.